Prevalence of Depression and its Associated Factors among Cancer Patients of Selected Hospital in Urban Area - Perke, Jyoti; Maniyar, Asif (Indian Journal of Nursing Sciences, 2024)
Objectives: The aim of the study was to assess the prevalence of depression and its associated factors among cancer patients and to find association between depression prevalence and its associated factors with selected demographic variables of cancer patients. Methods: The quantitative research approach with cross-sectional survey research design was used. 200 cancer patients who were diagnosed as cancer, above age of 18 years with clear consciousness, and willing to take part in the study were selected as samples using non-probability convenient sampling technique from selected hospital in urban area. Cancer patients who had history of psychiatric disorders were excluded in this study. The data have been collected using becks depression inventory II and self-report checklist. Results: The assessment of prevalence of depression in cancer patients in urban area indicated that 110 (54.73%) cancer patient had no depression, followed by 36 (17.91%) had moderate depression, 30 (14.93%) had borderline depression, 17 (4.86%) had severe depression, and very few 8 (3.98%) had extreme depression. Among demographic variables, family income was found to be associated with level of depression. Analysis of factors associated with depression indicated change in the job factor showed a significant association with gender, body image dissatisfaction showed a significant association with gender, alcohol intake was found to be significantly associated with gender and occupation. Conclusion: Effective management of the complicated side effects of cancer requires regular screening and comprehensive assessment for depressive disorders in clients with the disease. All healthcare providers caring for cancer clients including nurses, must emphasize not only the physical challenges but also psychological challenges of cancer.